Hepatitis B birth dose vaccination rates among children in Beijing: A comparison of local residents and first and second generation migrants. Issue 5 (3rd May 2016) - Chen, Ruohan; Li, Youwei; Wangen, Knut Reidar; Nicholas, Stephen; Maitland, Elizabeth; Wang, Jian
ABSTRACT: Providing hepatitis B vaccine to all neonates within 24 hours of birth (Timely Birth Dose, TBD) is the key preventative measure to control perinatal hepatitis B virus infection. Previous Chinese studies of TBD only differentiated between migrant and non-migrant (local-born generation-LG) children. Our study is the first to stratify migrants in Beijing into first generation migrants (FGM) and second generation migrants (SGM). Based on a questionnaire survey of 2682 people in 3 Beijing villages, we identified 283 children aged 0–15 years, from 246 households, who were eligible for a TBD. Multinomial logistic regression and statistical analyses were used to examine factors explaining TBD rates for LG, FGM and SGM children. Surprisingly, the TBD for LG Beijing children was not significantly different from migrant children. But after stratifying migrant children into FGM and SGM, revealed significant TBD differences were revealed across LG, FGM and SGM according to domicile (p-value < 0.001, OR = 3.24), first vaccination covered by government policy (p-value < 0.05, OR = 3.24), mother's knowledge of hepatitis B (p-value < 0.05, OR = 1.01) and the government's HBV policy environment (p-value < 0.05, OR = 2.338). Birthplace (p-value = 0.002, OR = 6.21) and better policy environments (p-value = 0.01, OR = 2.80) were associated with higher TBD rate for LG and SGM children. Compared with FGM children, SGM had a significantly poorer TBD rate (Fisher exact test of chi-square = 0.013). We identified SGM as a special risk group; proposed Hukou reform to improve SGM TBD; and called for Beijing health authorities to match TBD rates in other provinces, especially by improving practices by health authorities and knowledge of parents.